The tree, the man and the city: The case of seven maple trees in Veles - Violeta Bakalchev; Tasic Sasha; Mitko Hadzi Pulja; Minas Bakalchev (University American College Skopje, 2020)
The pronounced global crises caused by the effects of climate change is causing an essential need to rethink and redefine the basic assumptions about our relationship with nature. As more and more of the world's population lives in urban areas, the responsibility for the relationship to nature is increasingly shifted to urban contexts. The city had an ambivalent attitude toward nature and today we have to find the essential forms of mutual relation. he question of nature in the city today is still perceived through the quantitative relation between the green area and the built area where at what is missing is the essential personal relationship with the elements of nature. The relationship between man and the tree enters the deepest layers of its existence and reflects the continuous experience of dialogue with nature. This research will address the phenomenon of individual trees in public spaces that create specific areas of the city and their role in the spatial and symbolic support of neighborhoods. Through the example of the seven maples in the city landscape of Veles, we will explore the essential relationship among the man, the tree and the city. The six maples are the focal points of the urban texture. At the level of local neighborhoods, they are local centers. At the city level, they create a network of public places. They are the product of the traditional spatial social patterns through which the city was generated. The aim has been to document the cases of individual trees in the city, explain their relation and propose a methodology for reading this essential relationship. Drawing from the traditional cases of individual dominant trees as generative factors of human communities, we have pointed out the shared but also individual experience of correlations with nature as a common ground for reacting to climate change impact.
Keywords: 330; dominant trees; urban texture; social spatial patterns; nature; city; architecture